2009
DOI: 10.1128/jvi.01778-08
|View full text |Cite
|
Sign up to set email alerts
|

RING and Coiled-Coil Domains of Baculovirus IE2 Are Critical in Strong Activation of the Cytomegalovirus Major Immediate-Early Promoter in Mammalian Cells

Abstract: In recent years, baculovirus has emerged as a tool for high-efficiency gene transfer into mammalian cells. However, the level of gene expression is often limited by the strength of the mammalian promoter used. Here, we show that the baculovirus RING protein IE2 is a strong, promiscuous trans-activator in mammalian cells, dramatically upregulating the cytomegalovirus (CMV) promoter in both Vero E6 and U-2OS cells. Further study of the cellular mechanism for the activation led to the discovery of a novel IE2 nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 37 publications
1
53
0
1
Order By: Relevance
“…With the use of baculovirus IE2, expression of a foreign gene can be significantly boosted in some mammalian systems to further advance the application of baculoviruses [4]. We have identified the first viral factor that induces HSP expression upon baculovirus infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…With the use of baculovirus IE2, expression of a foreign gene can be significantly boosted in some mammalian systems to further advance the application of baculoviruses [4]. We have identified the first viral factor that induces HSP expression upon baculovirus infection.…”
Section: Discussionmentioning
confidence: 97%
“…Baculovirus IE2-an immediate early gene product-is responsible for turning on early and late genes during virus infection in insect cells [15][16][17]. Our previous study also found that IE2 forms novel nuclear body structures where transcription-related factors, such as RNA Pol II and actin, are concentrated for the strong activation of promoters in mammalian cells [4]. In this study, by purifying the IE2 nuclear bodies, we identified heat shock proteins as IE2 interaction proteins, which are crucial for the proper functioning of IE2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1995 (34), baculovirus has been used as a valuable and efficient tool for gene expression, tissue engineering, and gene therapy in mammalian cells or organisms (25,35). Further enhancement of baculovirus gene expression in these cells could be very useful for applications.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR fragments were inserted downstream of the mammalian cytomegalovirus (CMV) immediate early 1 promoter (p-CMV) on plasmid pAcL (25) to generate plasmids pAcLhr1, pAcLp143-3, pAcLp143-3.2, and pAcLp143-3.2a. All the constructs were verified by sequencing of the entire inserted fragments.…”
Section: Methodsmentioning
confidence: 99%